High–pressure electrical conductivity and Raman spectroscopy of chalcanthite. Issue 10 (26th November 2018) - Pu, Chang; Dai, Lidong; Li, Heping; Hu, Haiying; Zhuang, Yukai; Liu, Kaixiang; Yang, Linfei; Hong, Meiling
Abstract: The phase transitions and dehydration of chalcanthite were investigated by electrical conductivity and Raman spectroscopy at 1.0–24.0 GPa and 293–673 K in a diamond anvil cell. At ambient temperature, two secondary phase transitions were observed according to discontinuous changes in the slope of Raman shifts, full width at half maximum and electrical conductivities at ∼7.3 and ∼10.3 GPa. The dehydration temperatures were determined by the splitting of Raman peaks and changes in electrical conductivity as ∼350 and ∼500 K at respective ∼3.0 and ∼6.0 GPa. A positive relationship for chalcanthite between dehydration temperature and pressure is established.